Enabling and sustaining collaborative innovation - Thorsten Blecker; Nizar Abdelkafi; Christina Raasch (Hamburg University of Technology (TUHH), Institute for Technology and Innovation Management (TIM), 2008)
This paper extends the principles of open source software development to a non-industry-specific level by introducing the Open Source Innovation (OSI) model. OSI exhibits main differences to other related models and concepts such as the private-collective model, commons-based peer production, R&D networks and is therefore an innovation model in its own right. In order for OSI projects to be successful, numerous factors need to be fulfilled. We make the distinction between four categories of factors: economic, technical, legal, and social. In each category, we differentiate between enabling and sustaining factors. The enabling factors must be met at the beginning of the project, whereas the sustaining factors must be satisfied as the project progresses.
Keywords: 650